Upaya Meningkatkan Hasil Belajar Tentang Bilangan Ribuan Dengan Menggunakan Model Pembelajaran Take And Give Pada Mata Pelajaran Matematika Kelas IV Sekolah Dasar Negeri Megamendung 01 - Irman Irman; Supardi U.S (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Many teachers complain about the low learning outcomes of students in Mathematics lessons. This situation also occurred in grade IV at SDN Megamendung 01 related to learning the number of thousands. One of the causes of the lack of learning achievement is the lack of students' understanding of the number of thousands. As professional educators, teachers must be able to hold an active, creative, and fun learning process for students. Thus, it is hoped that it can encourage the improvement of student activities and learning outcomes through appropriate methods. This research was carried out at SDN Megamendung 01 Megamendung District, Bogor Regency from March to May 2025 in two cycles, involving 17 students, consisting of 8 boys and 9 girls. This research provides benefits both theoretically and practically for students, teachers, and related educational institutions. The order of learning improvement actions in the form of learning thousands of numbers from: (1) sorting numbers from small to large, (2) sorting the largest to the smallest using the number card tool in the teaching of Mathematics Class IV. The findings of the study show that there is an increase in student learning achievement through improving the learning process until the second cycle by applying the Tike And Give Learning Model. Learning achievement can be seen from the increase in final grades from the beginning of cycle I to cycle II. Where the average test score in the pre-cycle increased from 50.59 to 61.48 in the first cycle and to 80 in the second cycle. Therefore, it is hoped that teachers can improve their ability to manage the classroom and have an appropriate learning model to increase student participation and learning outcomes.